ANALISIS PENGARUH STRESS, WORKLOAD TERHADAP EMPLOYEES PERFORMANCE GENERASI MILENIAL DI KOTA BATAM DENGAN BURNOUT SEBAGAI VARIABEL MEDIASI - Yusuftan, Leonard Suryadi; Fatyandri, Adi Neka (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Employee performance has an important role in the success or failure of a company. Employee performance is a form of achievement produced by employees based on quantity, quality, time required, teamwork as a measure of the success of a company. The aim of this research is to analyze the effect of stress and workload on employee performance with burnout as a mediating variable. The type of research used in this research is using a quantitative approach. The research sample used was 385 respondents who were generation Y or the millennial generation born between 1980 and 2000 who were working in Batam City. Analysis of the data used in the research was by using the partial least squares structural equation model (PLS-SEM). The research results show that workload has a significant influence on stress. Workload and stress simultaneously also have a significant effect on burnout. Workload and stress have a significant effect on employee performance. The research also found that burnout did not have a significant effect on employee performance. Burnout also cannot mediate the relationship between workload and stress on employee performance.